2010
DOI: 10.3109/09638280903464497
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation of gait patterns of people with multiple sclerosis

Abstract: This study highlights typical gait patterns of people with MS and provides an indication of common pathways in the degeneration of ambulatory ability as a consequence of disease progression. This information should enable improved clinical treatment of ambulation, as well as the prescription, or even design, of appropriate assistive devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
129
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 18 publications
7
129
0
1
Order By: Relevance
“…Increased hip flexor moment at 'pull-off' is also likely to assist forward momentum to compensate for reduced ankle power at push-off which has been reported in people with MS compared with heathy controls [39,49]. The observed increases in positive work may also contribute to the 13 reported increase in effort and fatigue in people with MS, compared to healthy controls.…”
Section: Kineticsmentioning
confidence: 68%
See 2 more Smart Citations
“…Increased hip flexor moment at 'pull-off' is also likely to assist forward momentum to compensate for reduced ankle power at push-off which has been reported in people with MS compared with heathy controls [39,49]. The observed increases in positive work may also contribute to the 13 reported increase in effort and fatigue in people with MS, compared to healthy controls.…”
Section: Kineticsmentioning
confidence: 68%
“…This may indicate increased motor fatigue in the tibialis anterior muscle, which is susceptible to activity-induced fatigue in people with MS [11,14,38]. A delayed activation of the tibialis anterior muscle after initial contact in people with MS has also been previously measured [39], with reduced dorsiflexion angles observed in more mildly disabled groups of people with MS [40,41]. The less dorsiflexed position following the m6MWT may indicate a further delay of tibialis anterior activity upon loading [39].…”
Section: Kinematicsmentioning
confidence: 98%
See 1 more Smart Citation
“…1,6,8 Also reported are abnormalities in the joint angles of the hip, knee, and ankle 1,8,12 and kinetic abnormalities demonstrated by altered patterns of electromyography (EMG) activity during regular gait. 1,8,13 Of the multitude of abnormal gait parameters reported in MS, those that are most reliable and sensitive to subtle, clinically meaningful change may be of greatest value. Parameters related to gait variability may show promise in meeting these criteria.…”
mentioning
confidence: 99%
“…The tibialis anterior and vastus laterlias muscles exhibited delayed and increased activations during the initial contact period of the stance phase. The increased EMG activity that was apparent in the ankle and knee flexor muscles in the MS patient is thought to be a mechanism to counteract balance deficits and may have implications of both fatigue and spasticity [53]. The EMG curves of quadriceps and harmstring group muscles (Rectus T. Sarkodie-Gyan et al Femoris and Biceps Femoris respectively) showed some levels of weakness during the swing phase.…”
Section: Case Study: the Patient With Multiple Sclerosismentioning
confidence: 99%